2012
DOI: 10.1186/1471-2407-12-527
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer circulating tumour cells express a cell motility gene signature that predicts survival after surgery

Abstract: BackgroundMost cancer deaths are caused by metastases, resulting from circulating tumor cells (CTC) that detach from the primary cancer and survive in distant organs. The aim of the present study was to develop a CTC gene signature and to assess its prognostic relevance after surgery for pancreatic ductal adenocarcinoma (PDAC).MethodsNegative depletion fluorescence activated cell sorting (FACS) was developed and validated with spiking experiments using cancer cell lines in whole human blood samples. This FACS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 21 publications
3
50
1
2
Order By: Relevance
“…Through a metaanalysis of published human PDAC microarray data sets (74–77), we confirmed that overall YAP mRNA abundance was significantly increased in human PDAC when compared to normal pancreatic tissues (fig. S1A).…”
Section: Resultssupporting
confidence: 55%
“…Through a metaanalysis of published human PDAC microarray data sets (74–77), we confirmed that overall YAP mRNA abundance was significantly increased in human PDAC when compared to normal pancreatic tissues (fig. S1A).…”
Section: Resultssupporting
confidence: 55%
“…The researchers then performed whole-genome microarray analysis and identified a gene expression signature for motile CTCs. They found that high expression levels of the combination of the transforming growth factor-β gene and 9 other genes that regulate cell motility increased chances for disease-free survival (hazard ratio, 1.885 compared to patients with cells without this expression pattern) and overall survival (hazard ratio, 1.366 compared to patients with cells without this expression pattern) 106 .…”
Section: Ex Vivo Predictive Modelingmentioning
confidence: 98%
“…In a clinical trial (NCT00495924), Sergeant et al attempted to use gene expression signature of CTCs to predict survival for pancreatic cancer patients who underwent surgical tumor resection. The high co-expression of TGF-β1 and a group of 9 genes function in cell motility were found to be independent markers to predict the PFS and OS [17]. Taken together, many studies have reported promising results to support the use of CTCs as a prognostic marker in PC.…”
Section: Prognostic Values Of Pancreatic Ctcsmentioning
confidence: 74%
“…Sergeant and his colleagues registered the first CTC trial in PC in clinicaltrials.gov (NCT00495924). The aim of this study is to develop a CTC gene signature for assessing its prognostic relevance with surgical operation in PDAC patients [17]. Using FACS-based method, CTCs was enriched from the blood of 10 patients who underwent surgery for PDAC.…”
Section: Rapid Expansion Of Ctc Clinical Trials In Pcsmentioning
confidence: 99%